Genetic Variation of Structural and Functional Genes of SARS-CoV-2 Isolates Circulating in Banyumas (Indonesia) - Rovik, Anwar; Noviani, Clearensia Ade Bina (UIN Sunan Gunung Djati Bandung, 2023)
Scientists are performing various measurements to overcome the COVID-19 pandemic. The genomic mutations of SARS-CoV-2 can change their pathogenicity, infectivity, transmission, and antigenicity. This present study aimed to know a) the genetic variation of structural and functional genes of SARS-CoV-2 circulating in Banyumas and b) the potential of the Cilacap’s Harbour as a human mobility portal on the genetic variations of SARS-CoV-2 circulating in Banyumas, Central Java (Indonesia). Genomic sequence of SARS-CoV-2 isolates were taken from the Global Initiative on Sharing All Influenza Data (GISAID) and the National Center for Biotechnology Information (NCBI) online platforms. A gene cut was carried out from Wuhan reference isolate, fifteen isolates from Banyumas, and two isolates from Cilacap (Central Java) using Unipro UGENE v. 33.0 software, considering the annotation of the Wuhan-1 isolate. Genetic variations were detected among SARS-CoV-2 isolates circulating in Banyumas. The structural protein (envelope, membrane, nucleocapsid) encoding gene and the RdRp gene were highly conserved to Wuhan reference genome (Wuhan-Hu-1). Meanwhile, the ORF and the spike-encoding genes were less identical to the Wuhan reference genome. This study also proposed that human mobility from outside Central Java through Cilacap’s Harbour did not affect the genetic variation of SARS-CoV-2 isolates circulating in Banyumas (Central Java).